Data mining techniques and applications an introduction - Du, Hongbo (Course Technology/Cengage Learning, 2010)
This concise and approachable introduction to data mining selects a mixture of data mining techniques originating from statistics, machine learning and databases, and presents them in an algorithmic approach.